2015
DOI: 10.1016/j.radonc.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations from GEC ESTRO Breast Cancer Working Group (I): Target definition and target delineation for accelerated or boost Partial Breast Irradiation using multicatheter interstitial brachytherapy after breast conserving closed cavity surgery

Abstract: Providing guidelines based on the consensus of a group of experts should make it possible to achieve a reproducible and consistent definition of CTV (PTV) for Accelerated Partial Breast Irradiation (APBI) or boost irradiation after breast conserving closed cavity surgery, and helps to define it after selected cases of oncoplastic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 55 publications
1
64
0
2
Order By: Relevance
“…[13,14] Alco et al have shown that CTV BV dosage conformities change vary with the number of clips. [15] However, Kirwan et al have found that clips are not implanted for more than one-third of patients, in spite of benefits that have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] Alco et al have shown that CTV BV dosage conformities change vary with the number of clips. [15] However, Kirwan et al have found that clips are not implanted for more than one-third of patients, in spite of benefits that have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria, according to the Groupe Européen de Curiethérapie and the European Society for Radiotherapy & Oncology (GEC-ESTRO) recommendations on patient selection for APBI of low and intermediate risk groups were as follows: age ≥ 40 years, tumor size by final pathology ≤ 3 cm, negative axillary lymph nodes (sentinel or dissection), microscopically negative or close (≤ 2 mm) surgical margins, invasive ductal or lobular carcinoma, unicentric/unifocal tumors. Exclusion criteria consisted of younger age, tumors more than 3 cm in size, positive margins (presence of tumor tissue on surgical margins), axillary lymph nodes’ metastasis, presence of extensive intraductal component, multicentric/multifocal tumors [24, 25, 26, 27, 28]. All patients have signed informed consent before the treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Target definition and delineation was done according GEC-ESTRO Breast Cancer Working Group recommendations [26]. Post implantation CT images were transferred to BrachyVision treatment planning system (Varian Medical Systems, Inc., Palo Alto, CA, USA), on which the target volume segmentation and planning was performed.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth to mention that BT plays an important role in treating elderly patients, particularly unfit, frail, or sarcopenic, in which a conservative therapeutic approach may be the best choice [15]. Analyzing the international scenario in terms of cultural background, it becomes clear that there is an adequate attention and consideration towards BT, supported by the presence of dedicated guidelines, with regard to several anatomical sites issued by the main European [16,17,18,19,20,21,22,23,24,25] and American societies [26,27,28]. For this reason, it is sensible to correlate the cultural diffusion of the role and importance of BT at a national level, with its actual diffusion in the clinical practice [29,30,31,32,33,34,35,36,37,38].…”
Section: Airo Interventional Radiotherapy Study Group "State Of the Amentioning
confidence: 99%